Procedural Justice and Affirmative Action - Meshelski, Kristina (Ethical theory and moral practice, 2016)
There is widespread agreement among both supporters and opponents that affirmative action either must not violate any principle of equal opportunity or procedural justice, or if it does, it may do so only given current extenuating circumstances. Many believe that affirmative action is morally problematic, only justified to the extent that it brings us closer to the time when we will no longer need it. In other words, those that support affirmative action believe it is acceptable in nonideal theory, but not ideal theory. This paper argues that affirmative action is entirely compatible with equal opportunity and procedural justice and would be even in an ideal world. I defend a new analysis of Rawlsian procedural justice according to which it is permissible to interfere in the outcomes of procedures, and thus I show that affirmative action is not morally problematic in the way that many have supposed.